Exploring international post-graduate students' speaking experiences in an English as a Medium of Instruction (EMI) context - Huiling, Ma; Ismail, Lilliati (Society for Research and Knowledge Management, 2022)
This study aims to explore the practice of English as a medium of instruction (EMI) in Malaysia by investigating the experiences of international students enrolled in doctoral programs at the university level. In addition, the study provides an in-depth insight into the students' attitudes, the challenges they face, and the factors that influence academic English speaking. The authors also examine the implications of enhancing English as a Foreign Language (EFL) within the international post-graduate students' academic English-speaking experience in the Malaysian EMI context. This study adopted a qualitative approach. Data were collected using semi-structured interviews with 16 international doctoral students enrolled in various doctoral programs at a university in Malaysia. Data were coded and categorized according to themes using the NVIVO 12 software. The results show that there is a variety of challenges faced by the students in academic English speaking in an EMI context. Factors influencing their academic speaking include their past experiences and willingness to communicate. The study also suggests that lecturers should know that code-switching between English and Malay may impact international students' understanding and involvement in class.